PENDAMPINGAN MEMBUAT ALAT PEMBELAJARAN EDUKATIF DARI KULIT TELUR DAN BIJI-BIJIAN TERHADAP GURU DI SATUAN PENDIDIKAN ANAK USIA DINI MA’ARIF NU METRO - Ferdian Utama; Yuning Eka Rahma Wati; Fitri Yani (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2023)
This mentoring aims to improve the quality of early childhood education by utilizing teacher creativity and economically available resources. This assistance is implemented in early childhood education institutions in the Maarif NU Metro Lampung Education Institution unit. Through initial training, supporting materials, practical assistance, development of learning materials, evaluation, and experience sharing, teachers can become more competent in designing and using creative learning tools. This mentoring also brings benefits in terms of resource savings, improved learning quality, teacher skill development, and sustainability. This approach is an important step in improving the quality of early childhood education and motivating teachers to be more creative and innovative in teaching methods.